How Green Is My Plug-In?. - Voelcker, J. (IEEE spectrum)
A few analysts forecast that by 2020, plug-in vehicles, including plug-in hybrids and purely electric cars, will make up almost a third of new-car sales in the United States. And by 2050, plug-ins could account for most of China's burgeoning vehicular travel. But the environmental implications of such a massive shift are hardly straightforward. The complexity stems from the multiplicity of vehicles, electricity-generating technologies, and assumptions behind future projections for both. Imagine that two years from now you're comparing a newly available hybrid model that can recharge from wall current with a conventional gasoline car that consumes, say, 9.4 liters per 100 kilometers (25 miles per gallon). In this case, using grid power to drive electrically emits fewer greenhouse gases per kilometerrdquo under any circumstances. But if you compare the plug-in with an ultraeconomical European diesel or a conventional hybrid-electric like Toyota Motor Corp.'s Priusrdquo either of which burns just 4 to 5 L/100 kmrdquo the picture is more complicated: The plug-in emits fewer greenhouse gases in some circumstances, but more in others. The balance hangs on just what sort of power plants are being used to generate the electricity. So before you decide what to buy, you will need to answer a second question: How green is your grid?